2021
DOI: 10.3390/ma14040760
|View full text |Cite
|
Sign up to set email alerts
|

Modelling ATR-FTIR Spectra of Dental Bonding Systems to Investigate Composition and Polymerisation Kinetics

Abstract: Component ratios and kinetics are key to understanding and optimising novel formulations. This warrants investigation of valid methods. Attenuated Total Reflectance Fourier Transform Infra-Red (ATR)-FTIR spectra of separate primers/adhesives were modelled using summed spectra of solvents (water, ethanol), methacrylate monomers (HEMA (hydroxyethyl methacrylate), Bis-GMA (bisphenol A glycidyl methacrylate), and 10-MDP (10-methacryloyloxydecyl dihydrogen phosphate)), and fillers, multiplied by varying fractions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 51 publications
(83 reference statements)
4
37
0
Order By: Relevance
“…The difference spectra shown in this study confirm that the changes seen during the time of spectral acquisition are mainly due to the polymerisation reaction of methacrylates, corroborating findings from previous studies [ 11 , 13 ]. This is a simple and useful method to understand peak shifts during setting kinetics, although it can be used for a variety of different studies such as changes upon reaction of different materials, biological samples before and after treatment, material mixtures or aging processes [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The difference spectra shown in this study confirm that the changes seen during the time of spectral acquisition are mainly due to the polymerisation reaction of methacrylates, corroborating findings from previous studies [ 11 , 13 ]. This is a simple and useful method to understand peak shifts during setting kinetics, although it can be used for a variety of different studies such as changes upon reaction of different materials, biological samples before and after treatment, material mixtures or aging processes [ 49 , 50 ].…”
Section: Discussionsupporting
confidence: 91%
“…In methacrylates, polymerisation occurs with an opening of a carbon-carbon double bond, leaving a free valence available for reaction with other monomers, which may then co-polymerise. Absorbance changes include shifts in the 1700 cm -1 carbonyl region, loss of the 1635–1640 cm -1 [ v (C = C)] peak, and loss of the 1300–1320 cm -1 [ v (C-O)] doublet, with consequent shift to lower wavenumbers [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers 2021, 13, x FOR PEER REVIEW 3 of 12 improve a match with commercial fillers due to the composite having better esthetic properties and due to a potentially higher depth of cure [48,49]. Furthermore, the lower water sorption and water solubility of U-(bis-GMA)-Mod is due to its greater hydrophobicity, making it ideal for use as an adhesive system that requires more hydrophobic monomers [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…However, U-(GDMA)-Mod had a greater resistance than U-(bis-GMA)-Mod to leaching in organic solvents, and both monomers were free of BPA. The authors concluded that U-(bis-GMA)-Mod was better than U-(GDMA)-Mod in terms of its higher refractive index, which would improve a match with commercial fillers due to the composite having better esthetic properties and due to a potentially higher depth of cure [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%